Mechanisms of recycled fine brick aggregate in autogenous shrinkage mitigation, mechanical properties enhancement and microstructure improvement of alkali-activated slag-fly ash mortar. (10th April 2023) - Tian, Lingyu; Chen, Xin; Liu, Xu; Li, Hebin; Ge, Yong
Highlights: Internal curing by recycled fine brick aggregate (RFBA) is applied to mitigate the autogenous shrinkage of alkali-activated slag-fly ash (AASF). The workability, mechanical properties and microstructure of AASF incorporating RFBA are comprehensibly investigated. As well as self-desiccation, the reduction of steric-hydration force and the structural incorporation of alkali cations in C-A-S-H induce an enormous amount of autogenous shrinkage in AASF. Abstract: This study provides a profound comprehension of the influence of recycled fine brick aggregate (RFBA) as internal curing agent on autogenous shrinkage, mechanical properties and microstructure in the alkali-activated slag/fly ash (AASF) system. Specifically, the effects of RFBA on the setting time, flowability, compressive strength, flexural strength, autogenous shrinkage, and microstructure of AASF were investigated. The utilization of RFBA dramatically mitigates the autogenous shrinkage with an increase in compressive strength. As well as self-desiccation, the reduction of steric-hydration force and the structural incorporation of alkali cations in C-A-S-H are turned out to generate an enormous amount of autogenous shrinkage in AASF. In addition, it can be observed by the Nitrogen absorption test that the total pore volume is declined, and the pore structure is coarser with RFBA involved. Further, the phase composition acquired by X-ray diffraction (XRD) illustrates that the RFBA applied in AASF does not influence the type of reaction products but affects the quantity especially C-S-H and C-A-S-H gels. As Fourier transform infrared spectroscopy (FTIR) demonstrated, the polymerization degree of C-A-S-H gel is increased with the AASF containing of RFBA, and the chain length elongation of C-A-S-H is decreased.